ANALISIS COST VOLUME PROFIT SEBAGAI ALAT PERENCANAAN LABA (STUDI KASUS PADA UMKM DENDENG SAPI DI BANDA ACEH) - Alvini Hassanah; Rulfah M. Daud (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2019)
A company needs planning to assist management in assessing the level of profit to be gained, with a Cost Volume Profit analysis that focuses on the various factors that affect changes in the components of profit. This study aims to determine the application of CVP analysis as the basis of profit planning is expected 2018. The metodh used is descriptive method with empirical study approach. Researcher collets company information then do data analysis. CVP analysis is done by break even point (BEP), contribution margin (CM), margin of savety (MOS), operating laverage  (OL).  The  result  showed     by  Gunung  Seulawah  that  in  2017  the  contribution  margin  was  Rp.2.833.357.000,00,-,  minimum sales of 38.366 units or Rp. 9.207.736.265,- , break even point Rp 872.263.735,00,- with a total of as many as 3,634 units and operating laverage 1,09. The result showed  by Bungong Jaroe  that in 2017 the contribution margin was Rp. 1.102.573.000,,00,-,  minimum sales of 15.020 units or Rp.3.304.403.000,00- , break even point Rp. 655.596.999,00- with a total of as many as 2.980 units and operating laverage 1,20. The result showed  by Rencong Aceh that in 2017 the contribution margin was 95.580.300,.00,00,-,  minimum sales of 713 units or Rp. 171.179.274,00- , break even point Rp. 116,820,726,00- with a total of as many as 487 units and operating laverage 1,68. The companies set a profit of 15% over the previous year. To achieve expected profit, sales are targeted  at  Rp.  2.976.401.250,00-  for  Gunung  Seulawah  Rp. 1.058.042.263,00.-  Bungong  Jaroe  and  Rp.65.331.845,00,- Rencong Aceh. Mangement can apply CVP analysis to assist in planning earnings in the coming year.